2001
DOI: 10.1117/12.416949
|View full text |Cite
|
Sign up to set email alerts
|

<title>Temperature and pressure retrievals from O2 A-band absorption measurements made by ILAS: retrieval algorithm and error analyses</title>

Abstract: A visible grating spectrometer of the Improved Limb Atmospheric Spectrometer (ILAS) aboard the Advanced Earth Observing Satellite (ADEOS) measured atmospheric absorption spectra at a wavelength region from 753 nm to 784 nm, including the molecular oxygen (O 2 ) A-band centered at 762 nm, with a spectral resolution of 0.17 nm. Temperature and pressure profiles throughout the stratosphere were retrieved from the satellite solar occultation measurements of the O 2 Aband absorption spectra. Based on simulation stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Commonly probed absorption features include the γ -(0.63 μm), B-(0.69 μm), and A-(0.76 μm) rovibronic bands of O 2 , which have been used for wind measurements [1], in the determination of surface pressure [2][3][4] and aerosol and cloud properties [5][6][7][8], and for the retrieval of vertical profiles of pressure and temperature [9,10]. Among the various remote sensing experiments, those targeting the quantification of greenhouse gas concentrations (e.g., GOSAT [11], OCO-2 [12,13], CarbonSat [14]) are the most demanding because they require a relative standard uncertainty of less than 0.3% [12] in the atmospheric pressure profile retrieved from the O 2 A band.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly probed absorption features include the γ -(0.63 μm), B-(0.69 μm), and A-(0.76 μm) rovibronic bands of O 2 , which have been used for wind measurements [1], in the determination of surface pressure [2][3][4] and aerosol and cloud properties [5][6][7][8], and for the retrieval of vertical profiles of pressure and temperature [9,10]. Among the various remote sensing experiments, those targeting the quantification of greenhouse gas concentrations (e.g., GOSAT [11], OCO-2 [12,13], CarbonSat [14]) are the most demanding because they require a relative standard uncertainty of less than 0.3% [12] in the atmospheric pressure profile retrieved from the O 2 A band.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the instrument functions determined by the same method as given by Sugita et al 9 revealed some variation, which is anti-correlated with the instrument temperatures, as shown in Figure 1. The shifted value of the wavelength center is estimated to be 0.03 nm (1-pixel) per 10 degrees Celsius, which is the same value as was found from the ILAS measurement.…”
Section: Calibration Of Wavelength Center Of Instrument Functionsmentioning
confidence: 88%
“…9 This is explained by the high dispersion of the spectrometer and its optical layout, as given in Sugita et al 9 Sugita et al 9 have also developed a calibration method for changing the wavelength center as a function of the two optical parameters using well determined solar line database.…”
Section: Calibration Of Wavelength Center Of Instrument Functionsmentioning
confidence: 98%
See 2 more Smart Citations